2014
DOI: 10.1186/1757-1146-7-30
|View full text |Cite
|
Sign up to set email alerts
|

The assessment and management of diabetes related lower limb problems in India‐an action research approach to integrating best practice

Abstract: BackgroundIn this article the authors explore the current issues and barriers related to achieving successful outcomes to diabetic foot complications in India. This was achieved by engaging clinicians in taking ownership of the problems and facilitating them in the identification of solutions to action change in clinical practice.MethodsThis was accomplished through facilitating participants in this study via a process of problem identification and planning, the first phases of an action research cycle approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In addition, lack of time and energy and limited equipment was also found to be important factors affecting general practitioners' foot screening. Previous studies in different countries have also shown that limited time during healthcare professionals' consultations may result in foot assessments being overlooked [30][31][32], as macrovascular complications and HbA1c monitoring were the primary focus in busy practices. Although the number of general practitioners is constantly growing in China, it still cannot meet the screening needs of large populations of diabetic patients just like in other developing countries, and thus general practitioners may not be able to provide each patient with a full range of services [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lack of time and energy and limited equipment was also found to be important factors affecting general practitioners' foot screening. Previous studies in different countries have also shown that limited time during healthcare professionals' consultations may result in foot assessments being overlooked [30][31][32], as macrovascular complications and HbA1c monitoring were the primary focus in busy practices. Although the number of general practitioners is constantly growing in China, it still cannot meet the screening needs of large populations of diabetic patients just like in other developing countries, and thus general practitioners may not be able to provide each patient with a full range of services [33].…”
Section: Discussionmentioning
confidence: 99%
“…Harrison‐Blount et al. (2014) identified that routine foot examinations were not conducted, due to time restraints and resource limitations, unless the patients themselves drew attention to a foot problem. Whilst it is encouraging that footcare actions such as wound care, foot assessments, referrals to podiatry and specialist tertiary diabetic foot clinics became higher priorities for healthcare professionals in the presence of acute diabetes‐related foot complications, the International Working Group of the Diabetic Foot (IWGDF) promotes preventative strategies to support footcare and prevent ulcerations (Bus et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Effective implementation of change in foot care services, such as the use of new assessment tools, requires a tailored approach that is sensitive to the local factors affecting change. Previous work has identified the need to use different approaches, methods and therapeutic strategies in the Eastern (or Indian) context to achieve the goal of transferring evidence based guidelines [3][4][5]. Furthermore research has explored the need for understanding the values required to successfully embed evidence based practice [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the first paper of this series [5] researchers used an action research approach to illustrate the importance of process and engagement in driving change and the adoption of evidence based practices by those associated with foot health management in India. The work utilized the problem identification and action-planning phases of the action research process [5] in order to support change in foot care in one locality in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation